Evaluation of skin prick location on the forearm using a novel skin prick automated test device - Seys, Sven F.; Gorris, Senne; Uyttebroek, Saartje; Backaert, Wout; Jorissen, Mark; Schrijvers, Rik; Daems, Rembert; Loeckx, Dirk; Van Gerven, Laura; Hellings, Peter W. (Frontiers in Allergy, 2023)
The skin prick test (SPT) is the gold standard for identifying allergic sensitization in individuals suspected of having an inhalant allergy. Recently, it was demonstrated that SPT via a novel skin prick automated test (SPAT) device showed increased reproducibility and tolerability compared to conventional SPT besides other benefits.Objective: This study aimed at evaluating prick location bias using the novel SPAT device.The 118 volunteers, enrolled in the study, underwent SPAT with histamine (9 pricks) and glycerol control (1 prick) solutions on the volar side of the forearm. Imaging of the skin reactions was performed via the SPAT device and the longest wheal diameter was determined by the physician on the images in a web interface. Prick location bias was assessed along the medial vs lateral and proximal vs distal axes on the forearm.In total, 944 histamine pricks were analysed. Four medial and 4 lateral histamine pricks were grouped and wheal sizes were compared. Longest wheal diameters were not significantly different between medial and lateral prick locations (p=0.41). Furthermore, pricks were grouped by 2 based on their position on the proximal-distal axis on the forearm.There was no significant difference between the 4 groups of prick locations analysed (p=0.73).Prick location on the volar side of the forearm did not influence wheal size in SPAT pricked individuals.